Kebijakan Sistem Pembelajaran pada Tingkat Pendidikan MDTA di MDTA Al Khairat Tembung - Afrida Yanti; Nurana Dwina Bintang; Khairul Azmi; Ahmad Mukhlasin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses the learning system policy at the MDTA education level at MDTA Al Kairat Tembung. The method used is qualitative data through data collection through interviews with one of the sources as an instrument. The data analysis procedure carried out by reducing data, presenting data and drawing conclusions is one of the qualitative data techniques. The data collection technique used in this research was observation and interviews with a school principal at MDTA Al Kairat Tembung. The aim of research on a learning system policy at the MDTA education level at MDTA Al Kairat Tembung is because the learning system policy at the Madrasah Diniyah Takmiliyah (MDTA) education level is important in efforts to improve the quality of education. Several government policies related to curriculum, such as the Merdeka Curriculum, have been implemented to restore learning.